Morphology and properties of neutralized chitosan-cellulosenanocrystals biocomposite films - Corsello, Flavia Anahí (2016)
Chitosan/cellulose nanocrystals (CH-CN) films were obtained by casting of dispersions, and treated with NaOH for neutralization proposes. The composition of films was varied from 1 to 10 wt.% of CN. Changes in the morphology of the systems were correlated with the different properties studied. FTIR revealed the presence of a weak interaction between the polymer matrix and nanofiller, confirmed by a slightly increase in thermal stability. SEM images suggested that incorporating CN amounts higher than 3 wt.% generates phase-segregated systems, and SAXS showed that CH avoid the typical organization of CN at concentrations below 5 wt.%. Improved performance against water was obtained in composite materials comparing to the pure polymer matrix, as well as CH and CH-CN films did not show antibacterial activity demonstrating that remnant acetic acid, when no neutralization step is done, plays an important role in this property.